Informatics in Control, Automation and Robotics 8th International Conference, ICINCO 2011 Noordwijkerhout, The Netherlands, July 28-31, 2011 Revised Selected Papers - Ferrier, Jean-Louis; Bernard, Alain; Gusikhin, Oleg; Madani, Kurosh (Lecture Notes in Electrical Engineering, 2013)
The present book includes a set of selected papers from the eighth "International Conference on Informatics in Control Automation and Robotics" (ICINCO 2011), held in Noordwijkerhout, The Netherlands, from 28 to 31 July 2011. The conference was organized in four simultaneous tracks: "Intelligent Control Systems and Optimization", "Robotics and Automation", "Signal Processing, Sensors, Systems Modeling and Control" and "Industrial Engineering, Production and Management". The book is based on the same structure.   ICINCO received 322 paper submissions, not including those of workshops or special sessions, from 52 countries, in all continents. After a double blind paper review performed by the Program Committee only 33 submissions were accepted as full papers and thus selected for oral presentation, leading to a full paper acceptance ratio of 10%. Additional papers were accepted as short papers and posters. A further refinement was made after the conference, based also on the assessment of presentation quality, so that this book includes the extended and revised versions of the very best papers of ICINCO 2011.   Commitment to high quality standards is a major concern of ICINCO that will be maintained in the next editions of this conference, including not only the stringent paper acceptance ratios but also the quality of the program committee, keynote lectures, workshops and logistics.